2015
DOI: 10.4236/ajps.2015.69152
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Modeling of Oxidative Stress and C1 Metabolism Reveals Upregulation of Formaldehyde and Downregulation of Glutathione

Abstract: This research provides, to the authors' knowledge, the first integrative model of oxidative stress and C1 metabolism in plants. Increased oxidative stress can cause irreversible damage to photosynthetic components and is harmful to plants. Perturbations at the genetic level may increase oxidative stress and upregulate antioxidant systems in plants. One of the key mechanisms involved in oxidative stress regulation is the ascorbate-glutathione cycle which operates in chloroplasts as well as the mitochondria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…In Figure 8, an integrative molecular systems architecture is presented by coupling the dynamics of the molecular interaction in the heretofore known literature, accessible and aggregated by the authors, with the systems architecture of genetic modification, oxidative stress and C1 metabolism derived in earlier work [3]. As shown in Figure 8, glyphosate interacts with C1 metabolism by interfacing through the methionine biosynthesis pathway, which interfaces with both methionine biosynthesis and formaldehyde detoxification path- …”
Section: Systems Architecture Of Glyphosate Effect and Glutathione Symentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 8, an integrative molecular systems architecture is presented by coupling the dynamics of the molecular interaction in the heretofore known literature, accessible and aggregated by the authors, with the systems architecture of genetic modification, oxidative stress and C1 metabolism derived in earlier work [3]. As shown in Figure 8, glyphosate interacts with C1 metabolism by interfacing through the methionine biosynthesis pathway, which interfaces with both methionine biosynthesis and formaldehyde detoxification path- …”
Section: Systems Architecture Of Glyphosate Effect and Glutathione Symentioning
confidence: 99%
“…Moreover, the research identified the critical sub-systems of the oxidative stress system, and integrated oxidative stress models with C1 metabolism. Figure 3 shows the computational systems architecture of oxidative stress and C1 metabolism [3]. Interactions of oxidative stress system with C1 metabolism were computationally analyzed to understand the effect of oxidative stress on C1 metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…This research builds on three recent and specific efforts: 1) a systematic bioinformatics literature review of C1 metabolism [3], 2) in silico modeling of the C1 metabolism system [4], and 3) integrative modeling of oxidative stress and C1 metabolism [5]. A brief review of the results from that previous and recent research [4] [5], is provided below as a contextual basis for the research aim herein.…”
Section: Research Aimmentioning
confidence: 99%
“…A brief review of the results from that previous and recent research [4] [5], is provided below as a contextual basis for the research aim herein. In particular, the review of this research provides the baseline for understanding the temporal dynamics of key biomarkers associated with plant metabolism in non-GMOs.…”
Section: Research Aimmentioning
confidence: 99%
See 1 more Smart Citation